Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaan dengan Operating Performance Sebagai Variabel Moderating pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia - Riny Riny (Jurnal Wira Ekonomi Mikroskil, 2019)
The objective of the research was to analyze some factors which influenced firm value with operating performance as moderating variable in consumer goods companies listed in the Indonesia Stock Exchange. The research used associative causal design. The population was 39 consumer goods companies listed in the Indonesia Stock Exchange in the period of 2011-2014, and 26 of them were used as the samples. Secondary data were obtained from BEI website, www.idx.co.id. The data were gathered by conducting documentary study and analyzed by using multiple linear regression analysis for statistic analysis, while regression model had been tested in the classic assumption test. Independent variables were leverage, liquidity, profitability and size, while dependent variable was firm value and moderating variable was operating performance. The result of the research showed that, simultaneously, independent variables (leverage, liquidity, profitability and size) had significant influence on firm value. Partially, independent variables (leverage and liquidity) did not have significant influence on firm value, while independent variables (profitability and size) had significant influence on firm value. The result of residual test showed that the variable of operating performance was not proved to be moderating variable which could weaken the influence of leverage, profitability and size on firm value.